Implicit transitive inference and the human hippocampus: does intravenous midazolam function as a reversible hippocampal lesion? - Greene Anthony J (Behavioral and Brain Functions, 2007)
Abstract Recent advances have led to an understanding that the hippocampus is involved more broadly than explicit or declarative memory alone. Tasks which involve the acquisition of complex associations involve the hippocampus whether the learning is explicit or implicit. One hippocampal-dependent implicit task is transitive inference (TI). Recently it was suggested that implicit transitive inference does not depend upon the hippocampus (Frank, M. J., O'Reilly, R. C., & Curran, T. 2006. When memory fails, intuition reigns: midazolam enhances implicit inference in humans. Psychological Science, 17, 700–707). The authors demonstrated that intravenous midazolam, which is thought to inactivate the hippocampus, may enhance TI performance. Three critical assumptions are required but not met: 1) that deactivations of other regions could not account for the effect 2) that intravenous midazolam does indeed deactivate the hippocampus and 3) that midazolam influences explicit but not implicit memory. Each of these assumptions is seriously flawed. Consequently, the suggestion that implicit TI does not depend upon the hippocampus is unfounded.